A New Validated Stability Indicating RP-HPLC Method for Simultaneous Estimation of Pyridoxine Hydrochloride and Meclizine Hydrochloride in Pharmaceutical Solid Dosage Forms. (7th May 2013) - Nawaz, Md. Saddam
Abstract : A simple, specific, accurate, precise stability indicating reversed-phase high-performance liquid chromatographic (RP-HPLC) method was developed and validated for the simultaneous determination of pyridoxine hydrochloride (PYH) and meclizine hydrochloride (MEH). An isocratic separation of PYH and MEH were achieved on C 18, 250 × 4.6 mm ID, 5 μ m particle size columns at column oven temperature 37°C with a flow rate of 0.5 mL min −1 and using a diode array detector to monitor the detection at 254 nm. The mobile phase consisted of buffer : acetonitrile : trifluoroacetic acid at a ratio of 30 : 70 : 0.1 (v/v). The retention times of PYH and MEH was found to be 5.25 and 10.14 min, respectively. Suitability, specificity, linearity, accuracy, precision, stability, and sensitivity of this method for the quantitative determination of the drugs were proved by validation in accordance with the requirements laid down by International Conference on Harmonization (ICH) Q2 (R1) guidelines. The proposed method is reliable and robust and can be used as quality control tool for the estimation of these drugs in combined pharmaceutical solid dosage forms.